2015
DOI: 10.1007/s11011-015-9706-9
|View full text |Cite
|
Sign up to set email alerts
|

Early ALS-type gait abnormalities in AMP-dependent protein kinase-deficient mice suggest a role for this metabolic sensor in early stages of the disease

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by the selective loss of motoneurons. While the principal cause of the disease remains so far unknown, the onset and progression of the pathology are increasingly associated with alterations in the control of cell metabolism. On the basis of the well-known key roles of 5'-adenosine monophosphate-activated protein kinase (AMPK) in sensing and regulating the intracellular energy status, we hypothesized that mice with a genetic delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Inhibiting AMPK activity by raising cAMP levels also rescued TDP-43 mislocalisation in motor neuronal cells and delayed disease progression in TDP-43 WT mice [116]. Finally, AMPK a2 subunit gene ablation in mice was reported to induce gait disturbance that did not impact on motor symptoms in SOD1 G93A mice [64].…”
Section: Dysregulation Of Ampk Signalling In Alsmentioning
confidence: 91%
“…Inhibiting AMPK activity by raising cAMP levels also rescued TDP-43 mislocalisation in motor neuronal cells and delayed disease progression in TDP-43 WT mice [116]. Finally, AMPK a2 subunit gene ablation in mice was reported to induce gait disturbance that did not impact on motor symptoms in SOD1 G93A mice [64].…”
Section: Dysregulation Of Ampk Signalling In Alsmentioning
confidence: 91%
“…This viewpoint is supported by recent studies that investigated the consequences of the genetic ablation of AMPK, an enzyme that typically stimulates the consumption of fatty acids in skeletal muscle via the b-oxidation pathway. AMPK knockout mice exhibited gait disturbances reminiscent of that observed in the mutant SOD1 model (121). However, it should be taken into account that an enhanced oxidative metabolism, together with an excess of reactive oxygen species, would eventually lead to dysfunction of the respiratory electron transport chain, which would generate in itself more oxidative strees.…”
Section: Oxidative Stress and Mitochondrial Dysfunction Characterize mentioning
confidence: 98%
“…In this context, a critical role for PKCE has been demonstrated in the control neurites outgrowth (Chen & Tian, 2011;Shirai, Adachi, & Saito, 2008) and it has been reported that promoting axon regeneration could reduce the rate of skeletal muscle denervation and extend the life span of mice in a model of ALS (Jokic et al, 2006). The pathogenesis of ALS is also characterized by mitochondrial dysfunction and energy deficits (VandeVelde et al, 2011;Ioannides, Ngo, Henderson, Mccombe, & Steyn, 2016;Vergouts et al, 2015). Indeed, transplantation of neural precursors into the spinal cord of a mouse model of ALS gave rise to GFAP-positive donor cells that provided temporarily extended neuroprotection, improved motor function and prolonged animal survival times (Martin & Liu, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, transplantation of neural precursors into the spinal cord of a mouse model of ALS gave rise to GFAP-positive donor cells that provided temporarily extended neuroprotection, improved motor function and prolonged animal survival times (Martin & Liu, 2007). The pathogenesis of ALS is also characterized by mitochondrial dysfunction and energy deficits (VandeVelde et al, 2011;Ioannides, Ngo, Henderson, Mccombe, & Steyn, 2016;Vergouts et al, 2015). PKCd and PKCE participate in the control of cell energy homeostasis and an imbalance between these two PKCs is thought to disturb the flux of fuel entering the Krebs cycle and the overall production of energy (Gong et al, 2012).…”
Section: Discussionmentioning
confidence: 99%